Quality Assurance of Medicines: Main Scientific Approaches and Control Methods - E. L. Kovaleva; Yu. A. Zolotov; D. V. Somov (Регуляторные исследования и экспертиза лекарственных средств)
The most important component of national health policy is the assurance of quality, efficacy, and safety of medicines entering the pharmaceutical market in the Russian Federation. In this interview, we have discussed the quality control of medicines; its interconnections with various branches of science, in particular, with analytical chemistry; and the matters of material and equipment supply with Elena L. Kovaleva (Doctor of Pharmaceutical Sciences, Deputy Director of the Centre for Medicinal Products Evaluation and Control of the Scientific Centre for Expert Evaluation of Medicinal Products of the Ministry of Health of the Russian Federation), Yuri A. Zolotov (Academician of the Russian Academy of Sciences, Full Professor, Doctor of Chemical Sciences), and Dmitry V. Somov (Candidate of Pharmaceutical Sciences, Acting Director General of the Information and Methodological Center for Expertise, Accounting, and Analysis of the Circulation of Medicinal Products of the Federal Service for Surveillance in Healthcare).